AL-HÂJÂT AL-TADRÎBIYAH LI MU'ALLIMÎ AL-LUGHAH AL-'ARABIYAH FÎ INDONESIA WA 'ALÂQATUHÂ BI AL-JINS WA AL-MUAHAL AL-'ILMÎ - Bahruddin, Uril; Al-Amir, Muhammad Abdullah; Ramadhan, Muhammad Fadli (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
Among the problems of learning Arabic in Indonesia is the low pedagogic competence of teachers, which can be improved by attending regular and planned training. The purpose of the article is to understand (1) the need for Arabic teachers for instructional training (2) to measure the correlation between teacher needs and training with gender and educational background. This research is descriptive quantitative, using a questionnaire instrument. Data analysis using the SPSS program. The results showed a significant difference between the mean score of the study sample and the hypothetical mean in lesson planning. There is a significant difference between the average score of the study sample and the hypothetical average in the implementation of the lesson. There is a significant difference between the mean score of the study sample and the hypothetical mean in the learning technique. There was no significant difference between the samples in Arabic teacher training needs other than the gender variable. There is a significant difference between the Bachelors and Masters groups in learning technology, and not in other educational backgrounds.